Du modèle australien au modèle canadien - Pelletier, Réjean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
In recent years, many political analysts as well as the Special Joint Committee on the Reform of the Senate have been proposing the Australian system as a model for the reform of the Canadian Senate. Some of the proposals of the Joint Committee, and their implications, are discussed here, particularly proposals concerning how senators are elected, duration of their mandate, and the powers of the Senate. One important problem about an elected Senate is that the senators might rapidly become more preoccupied with party lines than with an adequate representation of regional interests.